Regards sur un paysage anglais : « Seascape » de W.H. Auden à Benjamin Britten - Nathalie Vincent-Arnaud (Revue LISA)
This article aims to bring to light the close links that bind together W.H. Auden’s poem “Seascape” and other artistic languages such as painting and music since the poem was actually set to music by Benjamin Britten. In keeping with this inter-semiotic approach, the main structural and rhetorical elements of the poem will be discussed, and more particularly the stylistic devices that the musical work itself seems to echo through a combination of rhythmical, melodic and harmonic patterns which all serve to enhance the suggestive power of the text. We will try to define more precisely the intricate artistic heritage of the poem through which the reader both hears and sees the whole scene conjured up.